Company Financial Performance: An Examination of Financial Ratios at PT Pelni Baubau Branch - Janna Meilani Ode; Filasti Rahma; Andriani Saputri (International Journal of Multidisciplinary Learners, 2024)
The purpose of this study is to determine the financial ratios in measuring the financial performance of PT Pelni Baubau Branch in accordance with industry standards. The data source technique used, namely documentation and literature study used for this study is quantitative and uses financial ratio analysis such as liquidity, solvency, activity, and profitability. The study results show that: 1) The financial performance of PT Pelni Baubau Branch in 2019-2023 is not good as measured using liquidity ratio analysis, namely the current ratio. This shows that the company has difficulty in meeting its current debt with available current assets. 2) The financial performance of PT Pelni Baubau Branch in 2019-2023 is good as measured using the solvency ratio analysis, namely the debt to equity ratio. This shows that the company has a very conservative capital structure and is mostly financed by equity rather than debt. 3) The financial performance of PT Pelni Baubau Branch in 2019-2023 is not good as measured using the activity ratio analysis, namely total assets turnover. This shows that the company is less likely to generate sales based on fixed assets owned. The financial performance of PT Pelni Baubau Branch in 2019-2023 is not good as measured using profitability analysis, namely return on equity. This shows an increase in total equity that is greater than the previous year, but is unable to generate the highest company profits.